HISTORIOGRAFI KAUSA LEGAL BUNGA (RIBA) DI INDONESIA - Fanani Mafatikul Ihsan; Ridan Muhtadi; Moh Subhan (Ulumuna: Jurnal Studi Keilsman, 2020)
The discourse on interest can be said to be a "classic" problem both in the development of Islamic thought or in the history of human civilization. Because interest can not be separated from the economic activities of humanity. In Indonesia, interest has become transactions in the economic field in general. Until now interest collection still occurs in various commercial activities, both in the sale and purchase activities, accounts payable and other transactions. In Islamic teachings, economic activities carried out by humans have some rules and ethics or morality in Islamic law. However, the stipulation of interest as usury still needs an in-depth study, especially in terms of the history of legality stipulated in a fatwa in Indonesia.